Carbon dioxide activated carbide-derived carbon monoliths as high performance adsorbents - Oschatz, Martin; Borchardt, Lars; Senkovska, Irena; Klein, Nicole; Leistner, Matthias; Kaskel, Stefan (Carbon, 2013)
Carbide-derived carbon (CDC) monoliths (DUT-38) with a distinctive macropore network are physically activated using carbon dioxide as oxidizing agent. This procedure is carried out in a temperature range between 850 and 975 °C with durations ranging from 2 to 6 h. Resulting materials show significantly increased specific surface areas as high as 3100 m2/g and total (micro/meso) pore volumes of more than 1.9 cm3/g. The methane (214 mg/g at 80 bar/25 °C), hydrogen (55.6 mg/g at 40 bar/-196 °C), and n-butane (860 mg/g at 77 vol.%/25 °C) storage capacities of the activated CDCs are significantly higher as compared to the non-activated reference material. Moreover, carbon dioxide activation is a suitable method for the removal of metal chlorides and chlorine residuals adsorbed in the pores of CDC after high temperature chlorination. The activation does not influence the hydrophobic surface properties of the CDCs as determined by water adsorption experiments. The macropore network and the monolithic shape of the starting materials can be fully preserved during the activation procedure. n-Butane breakthrough studies demonstrate the materials applicability as an efficient hydrophobic filter material by combining excellent materials transport with some of the highest capacity values that have ever been reported for CDCs. © 2013 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20